A Model Driven Framework for Portable Cloud Services - Aparna Vijaya; Neelanarayanan V (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Cloud Computing is an evolving technology as it offers significant benefits like pay only for what you use, scale the resources according to the needs and less in-house staff and resources. These benefits have resulted in tremendous increase in the number of applications and services hosted in the cloud which inturn has resulted in increase in the number of cloud providers in the market. Cloud service providers have a lot of heterogeneity in the resources they use. They have their own servers, different cloud infrastructures, API’s and methods to access the cloud resources. Despite its benefits; lack of standards among service providers has caused a high level of vendor lock-in when a software developer tries to change its cloud provider. In this paper we give an overview on the ongoing and current trends in the area of cloud service portability and we also propose a new cloud portability platform. Our new platform is based on establishing feature models which offers the desired cloud portability. Our solution DSkyL uses feature models and domain model analysis to support development, customization and deployment of application components across multiple clouds. The main goal of our approach is to reduce the effort and time needed for porting applications across different clouds. This paper aims to give an overview on DSkyL.